Comparison of Outcome in Unilateral and Bilateral Sphinctorotomy in Patients of Haemorrhoidectomy - Ayesha Rehman, Rabail Rana, Kamran Liaquat, Farheen Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
The anal canal is the site of the dilated veins known as haemorrhoids. They’re essential for achieving and maintaining complete continence. In the anal canal, they can be either internal or external. Haemorrhoids can cause pain, pruritis, mucous discharge, mucosal prolapse, bleeding (which is often painless), and brilliant red haemorrhage. 2 There are four different types of haemorrhoids, ranging from first degree (just bleeding) to fourth degree (prolapse and stay reduced on reduction) (permanently prolapsed).3 Even though every case of haemorrhoids bleeds, there are different categories based on how far the haemorrhoids have prolapsed. Only when things get complicated do you see any signs. 4 Objective and Methodology: This research aims to compare the rates of pain experienced by patients after undergoing haemorrhoidectomy, lateral internal sphincterotomy, and bilateral internal sphincterotomy. A Randomized Controlled Trial (RCT) study design was used for this investigation. The investigation took place at the Surgery Department of Allied Hospital in Faisalabad (March to September 2021). In all, 140 patients aged 25-65 with severe haemorrhoids (grades III and IV) were chosen. Any neurological deficiency or chronic pain syndrome, renal disease, or bleeding disorders, as well as patients with recurring haemorrhoids or other anorectal pathology (fistula in ano, anal fissures, etc.), were not included in the study. Hemorrhoidectomy with bilateral internal sphincterotomy (Group BL) and hemorrhoidectomy with lateral internal sphincterotomy (Group UL) were performed on patients. After 24 postoperative hours, all patients were evaluated for postoperative pain. Results: Patients in Group BL had a mean age of 45.36 10.33 years, whereas those in Group UL had a mean age of 43.94 10.22 years. A whopping 76 (54.29%) of the patients fell within the 25-45-year-old age range. The ratio of male to female patients was 2.1:1, with 95 males (67.86%) and 45 females (32.14%) in a total of 140 patients. Pain was experienced by 4 (5.71%) of my patients following haemorrhoidectomy with bilateral internal sphincterotomy and by 25 (35.71%) of my patients following haemorrhoidectomy with lateral internal sphincterotomy (p 0.0001). Conclusion: Patients undergoing hemorrhoidectomy were less likely to experience postoperative pain if bilateral internal sphincterotomy was performed. Keywords: Haemorrhoids, internal sphincterotomy, post-operative pain.